Analysis of Problem Solving Ability in Quadrilateral Topic on Model Eliciting Activities Learning Containing Ethnomathematics - Ilyyana, Kharisma; Rochmad, Rochmad (Universitas Negeri Semarang, 2018)
The low ability to solve mathematics problems and the character of local cultural love is due to lack of habituation in problem-solving that is associated with everyday life situation and the learning model used is not in accordance with local cultural values. This study aims to analyze the validity, the practicality, the effectiveness of the learning tools implementation, and the characteristics of the problem-solving ability of learners on the learning of MEA with ethnomathematics. The research method used was mixed method of concurrent embedded model. At the beginning of the study was given an initial problem-solving test in experiment and control classes as well as giving a questionnaire of the love of local culture in the experimental class, then the experimental MEA learning was carried out on the experimental class and the PBL learning in the control class. At the end of the study, final tests on the problem-solving ability was conducted in experimental and control classes as well as giving a local love questionnaire in the experimental class. The results showed that the MEA learning containing ethnomathematics on quadrilateral topics is valid, practical, and effective. The results of the characteristics of the problem-solving abilities analysis of the upper group, students have been able to solve the problem properly according to Polya's steps, the problem-solving ability of students in the middle group is still difficult in the step of calculating, while the students in the lower group have difficulty in planning a solution.